Design of high gain microstrip Yagi array antenna for avalanche radar - Mohd. Isa, Farah Nadia; Brennan, P.V. (2012)
This paper presents the design and construction of a microstrip Yagi array antenna operating at 5.3 GHz, to be used with an avalanche sensor in avalanche measurement. The advantage of the antenna is it can achieve a high gain of 15.2 dB with bandwidth of 8% in compact size. The gain enhancement is achieved by using a compact microstrip Yagi antenna as the array element; separating the feed network from the main radiating elements; and increasing the antenna height by installing the feed layer at the back of the patch layer, sharing the same ground plane. In order to ensure the power is transferred smoothly from the main input port to the radiating elements, the corporate feed is also design and tested. The fabricated antenna shows an agreeable performance with the simulated version.